2021
DOI: 10.3389/fpsyg.2021.639191
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in Depressive Behavior Among Forensic Psychiatric Patients

Abstract: BackgroundWomen are almost twice as likely to develop depression than men, but men commit suicide more often. One explanation for this paradox is that current depression inventories do not fully capture typical male symptoms of depression. Several studies showed that most depression symptoms in men are masked by externalizing behaviors, such as aggressiveness, addiction, and risky behavior. Here, we explored the differences in depression symptoms between men and women in a forensic psychiatric sample.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…A huge German survey showed that women more often consult psychiatrists or psychotherapists than men [ 66 ]. These differences may be driven by the masculine role model, which inhibits help-seeking behavior [ 67 ]. Such a mechanism might also explain this study’s findings that patients with masculine depression (both women and men) show fewer health services contacts.…”
Section: Discussionmentioning
confidence: 99%
“…A huge German survey showed that women more often consult psychiatrists or psychotherapists than men [ 66 ]. These differences may be driven by the masculine role model, which inhibits help-seeking behavior [ 67 ]. Such a mechanism might also explain this study’s findings that patients with masculine depression (both women and men) show fewer health services contacts.…”
Section: Discussionmentioning
confidence: 99%
“…They are also consistent with the world risk ratio of 3.2 for sex, with higher rates for older men (Martini et al, 2019; WHO, 2014). Gender-related differences could result from poor ability to diagnose depressive symptoms in men (Streb et al, 2021). This hypothesis arises from the evidence that suicide can be associated with depressive symptoms, and that women, who are diagnosed as suffering from depression more frequently than men, die less from suicide than men.…”
Section: Discussionmentioning
confidence: 99%
“…Jednak w innych, niemieckich badaniach obliczono również współzależność GSDS z BDI II, a wyniki były porównywalne do naszych, w których użyto BDI. Wynik ogólny GSDS 26 u mężczyzn korelował w tym badaniu z BDI II na poziomie r = 0,69, a spośród podskal odnotowano najsilniejsze związki BDI II z depresyjnością (r = 0,73) [38].…”
Section: Podsumowanieunclassified